Association of serum folate with prevalence of non-alcoholic fatty liver disease among adults (NHANES 2011–2018) - Yao, Baodong; Lu, Xiaojing; Xu, Lai; Jiang, Yun (Frontiers in Nutrition, 2023)
Background: Folate was involved in oxidative stress, hepatic lipid metabolism and chronic hepatic inflammation. However, evidence about the association between serum folate level and non-alcoholic fatty liver disease (NAFLD) in general population is scarce. This study aimed to explore the relationship between serum folate level and NAFLD among adults. Methods: 7146 adult participants aged 20 years and over who have complete data of serum folate level and liver function biomarkers in NHANES 2011-2018 were included. Serum folate level was measured by isotope-dilution high-performance liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). And suspected NAFLD was defined according to the United States fatty liver index (USFLI). Logistic regression and the restricted cubic spline models were performed. Results: Serum folate level was inversely associated with the presence of NAFLD. When comparing the second, third and fourth quartiles of serum folate level to the lowest quartile, the adjusted ORs of the presence of NAFLD were 0.62 (0.49-0.78), 0.65 (0.51-0.84), and 0.43 (0.32-0.56) respectively (P for trend< 0.001). The non-linear and L-shaped relationship was found between serum folate level and the presence of NAFLD in the restricted cubic spline regression (P for non-linearity < 0.01). Consistent with serum total folate, serum 5-MTHF level was also inversely associated with the presence of NAFLD. Conclusion: Higher serum folate level may be negatively associated with NAFLD.